Prevalence of snoring and symptoms of sleep-disordered breathing in primary school children in Istanbul - ARMAN, AYŞE; KARADAĞ, BÜLENT TANER; SAVE, DİLŞAD (AMER COLL CHEST PHYSICIANS, 2004)
Study objectives: Snoring during sleep is an important manifestation of obstructive sleep apnea syndrome (OSAS). Although clinical history is not sufficiently sensitive and specific to distinguish primary snoring from OSAS, snoring is indicative of upper airway obstruction and may be associated with the presence of diurnal symptoms. Our study aims were to determine the prevalence of snoring in primary school children in Istanbul, and to evaluate the diurnal symptoms and conditions that may be associated with sleep problems. Design, setting, and subjects: A parental questionnaire was used to assess the sleep and wake behavioral patterns in children. Eight representative schools in each of 9 school districts randomly selected from the 32 school districts in Istanbul were visited. Results: The response rate was 78.1%; 2,147 of 2,746 questionnaires were fully completed, returned, and analyzed. The prevalence of habitual snoring was 7.0%. Habitual snorers had significantly more nighttime symptoms, such as observed apneas (odds ratio [OR], 16.9; 95% confidence interval [CI], 10.0 to 28.8; p < 0.0001), difficulty breathing (OR, 17.8; CI, 10.9 to 29.2; p < 0.0001), restless sleep, parasomnias, and nocturnal enuresis, compared to occasional and nonsnorers. There were also increased prevalence of daytime symptoms, such as falling asleep while watching television (OR, 1.8; CI, 0.9 to 3.7; p = 0.01) and in public places (OR, 2.1; CI, 1.2 to 3.8; p = 0.03), and hyperactivity (OR, 2.7; CI, 1.8 to 3.9; p < 0.0001). Exposure to cigarette smoke and the presence of asthma and hay fever increased the likelihood of habitual snoring. Children with a higher risk for OSAS (habitual snoring, apnea, and difficulty breathing during sleep) were also compared to nonsnorers. Although nighttime symptoms were more likely in the high-risk group, the risk of daytime symptoms increased as well. Conclusions: Habitual snoring is a significant problem for children and may be associated with diurnal symptoms. Exposure to cigarette smoke at home and the presence of asthma and hay fever increase the likelihood of habitual snoring.
Keywords: children; hyperactivity; passive smoke exposure; prevalence; snoring; APNEA SYNDROME; NOCTURNAL HYPOXEMIA; PRESCHOOL-CHILDREN; PERFORMANCE; DISTURBANCE; ASSOCIATION; BEHAVIOR; SMOKING